SOCIAL SECURITY FOR WOMEN IN THE INDIAN SOCIAL SYSTEM - A.ARULMATHY1; Dr. VINAYAGAMURTHY (RADJA PUBLIKA, 2023)
ABSTRACT India, renowned for its rich cultural heritage, assigns women the revered role of goddess Lakshmi. However, recent years have witnessed a surge in crimes against women, raising concerns about their safety and security. Incidents of crimes against women occur regularly, reflecting a decline in the status of women from ancient to modern times. In today's advanced era, women of all ages and backgrounds face daily threats such as assault, workplace harassment, abduction, domestic violence, and various forms of exploitation. Despite constitutional provisions guaranteeing women equal rights, dignity, and freedom from gender discrimination, the practical implementation of these regulations is hindered by societal attitudes. This abstract explores the challenges surrounding women's safety in India, emphasizing the need for a shift in public perception and the enforcement of existing laws.